KONFLIK BATIN TOKOH UTAMA DINA NOVÉL PANGANTÉN KARYA DÉDÉN ABDUL AZIZ (Ulikan Struktural jeung Psikologi Kapribadian Humanistik) - Ane Ainun Nurlaela, - (2021)
This research discusses several conflicts that often occur in real life. This research needs to be done to overcome problems in literacy crises, especially regarding literary psychology. The purpose of this research is to describe the structure of the story using Robert Stanton's theory (themes, story facts, literary means) with Abraham Maslow's theory of the humanistic psychology of personality. The method used is descriptive analysis with literature study techniques. The results of the research in the theme of Panganten's novel are memories that make sick, lose someone who is very loved, the desire to live in freedom, hopelessness, the destiny that cannot be denied, a mother's worries, to feel life in solitude. The plot in this story has four episodes and uses an advanced plot. The characters in this story have one main character and seven additional characters. The setting in this story is divided into three parts, there are eleven place settings, twelve-time settings, and three social settings. The title in the Panganten novel describes the whole content of the story. The author's point of view uses the first-person method as the main character. The language styles contained in the Panganten novel include (ngumpamakeun, mijalma, rarahulan, kadalon, rautan, lalandian, ngasor). In the Panganten novel conflict that is needed by the main character is all levels of human needs that are included in the psychological theory of humanistic personality which includes physiological needs, sense of security needs, love needs, self-esteem needs, and self-actualization needed.